Population-Based Estimates of Physical Activity for Adults with Type 2 Diabetes: A Cautionary Tale of Potential Confounding by Weight Status - Ronald C. Plotnikoff; Steven T. Johnson; Constantinos A. Loucaides; Adrian E. Bauman; Nandini D. Karunamuni; Michael A. Pickering (Hindawi Limited, 2011)
At a population level, the method used to determine those meeting physical activity guidelines has important implications, as estimating "sufficient" physical activity might be confounded by weight status. The objective of this study was to test the difference between three methods in estimating the prevalence of "sufficient activity" among Canadian adults with type 2 diabetes in a large population sample (N=1614) while considering the role of weight status as a potential confounder. Our results revealed that estimates of physical activity levels vary by BMI categories, depending on the methods examined. Although physical activity levels were lower in the obese, their energy expenditure estimates were not different from those who were overweight or of a healthy weight. The implications of these findings are that biased estimates of physical activity at a population level may result in inappropriate classification of adults with type 2 diabetes as "sufficiently active" and that the inclusion of body weight in estimating physical activity prevalence should be approached with caution.